ASSESSMENT OF THE AESTHETIC ATTRACTIVENESS OF THE HIGHLAND LANDSCAPE ZONES: (on example of the Syunik Region) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In the article a special methodology of obtaining an objective aesthetic estimation was given. As well as an analysis of aesthetic territories attractiveness by highland landscape zone was done. As a result, the most attractive areas are widely spread in the low and middle mountain forest zones.
Keywords: aesthetic attractiveness; Syunik Region; methodology; assessment; map; landscape zones